Histórias de empoderamento: um estudo sobre o processo vivenciado por mulheres que ocupam cargos de alto escalão na administração pública e de empresas em Belo Horizonte - Gizelle de Souza Mageste (2008)
This research aimed to understand the process of empowerment of executive women in government and business in Belo Horizonte. Through interviews of life history were investigated the experiences of women interviewed and seeking to understand the process undertaken by them in pursuit of autonomy and empowerment. The resultsrevealed that the process of empowerment is very complex and goes far beyond the mere inclusion of women in the labour market, the career development and financial independence. It was noticed that the process of empowerment goes expanding and incorporating results from the action of the woman as subject of his own life, through their interpersonal relations to a transformation that occurs in any context in which it isembedded. The stories of life studied show that the respondents had an intense dedication to education, built networks of relationships that served as a support to advance its quest, consciously chose a husband who does not fear a empowered woman, organized their time to give account of meet all its activities in the public sphere and also in the private sphere. Finally, it appears that the study of the process ofempowerment of women is a field large, sparsely explored and should be better investigated in future research.